Fiqh Analysis of Cryptocurrency Through the Istihsan Method Approach: A Study of Feasibility as an Asset or Sil'ah in a Sharia Perspective - Madani, Farid; Nurhikmah, Aulia (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the legal status of cryptocurrency using the istihsan method in Islamic jurisprudence and analyzes its position within Indonesia’s positive legal framework. Cryptocurrency is defined as a digital asset based on blockchain technology that lacks physical form but possesses economic value and tradable utility. A normative legal research approach is employed, integrating conceptual, theological, and maqāṣid al-sharī‘ah perspectives. The scope of the study focuses on the feasibility of categorizing cryptocurrency as sil’ah (a lawful commodity) and its regulatory compliance in the national legal system. The findings indicate that cryptocurrency may be considered permissible as a commodity when it fulfills the requirements of clear utility, lawful ownership, and absence of excessive gharar or qimar; however, it remains prohibited as a medium of payment replacing the Indonesian Rupiah. Under Indonesian law, crypto assets occupy a dual status: illegal as a form of legal tender, yet legal as a traded commodity regulated by Bappebti, with mandatory consumer protection and Anti-Money Laundering and Counter-Terrorism Financing (AML-CTF) measures. The major challenges concern price volatility and vulnerabilities to cybercrime and financial abuses. Practical implications underscore the need for adaptive regulation, Sharia-compliant due diligence standards, and improved public financial literacy. This research advances contemporary Islamic legal studies by establishing istihsan as a methodological framework for addressing digital economic transformation, while offering normative support for strengthening sharia-compliant crypto regulation in Indonesia.